Performance of lung cancer screening with low‐dose CT in Gejiu, Yunnan: A population‐based, screening cohort study - Meng‐Na Wei; Zheng Su; Jian‐Ning Wang; Maria J. Gonzalez Mendez; Xiao‐Yun Yu; Hao Liang; Qing‐Hua Zhou; Ya‐Guang Fan; You‐Lin Qiao (Thoracic Cancer)
Background The performance of lung cancer screening with low‐dose computed tomography (CT) (LDCT) in China is uncertain. This study aimed to evaluate the performance of LDCT lung cancer screening in the Chinese setting. Methods In 2014, a screening cohort of lung cancer with LDCT was established in Gejiu, Yunnan Province, a screening center of the Lung Cancer Screening Program in Rural China (LungSPRC). Participants received a baseline screening and four rounds of annual screening with LDCT in two local hospitals until June 2019. We analyzed the rates of participation, detection, early detection, and the clinical characteristics of lung cancer. Results A total of 2006 participants had complete baseline screening results with a compliance rate of 98.4%. Of these, 1411 were high‐risk and 558 were nonhigh‐risk participants. During this period, 40 lung cancer cases were confirmed, of these, 35 were screen‐detected, four were post‐screening and one was an interval case. The positive rate of baseline and annual screening was 9.7% and 9.0%, while the lung cancer detection rate was 0.4% and 0.6%, respectively. The proportion of early lung cancer increased from 37.5% in T0 to 75.0% in T4. Adenocarcinoma was the most common histological subtype. Lung cancer incidence according to the criteria of LungSPRC and National Lung Cancer Screening Trial (NLST) was 513.31 and 877.41 per 100 000 person‐years, respectively. Conclusions The program of lung cancer screening with LDCT showed a successful performance in Gejiu, Yunnan. However, further studies are warranted to refine a high‐risk population who will benefit most from LDCT screening and reduce the high false positive results. Key points This study reports the results of lung cancer screening with LDCT in Gejiu, Yunnan, a high‐risk area of lung cancer, and it demonstrates that lung cancer screening with LDCT is effective in detecting early‐stage lung cancer. Our program provides an opportunity to explore the performance of LDCT lung cancer screening in the Chinese context.